Ngamen Kreatif Ujud Sutrisno - Bondet Wrahatnala (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2006)
Creativity is inseperable from human l~fe, including the fulJIlment of human needs. For this goal, man carries out ailforms of activities in accordance with abilities to support the profession of this choice. This is true in the case of Sujud Sutrisno, a street musician who has been creative and consistent in carying out his profession for 28 years. Sujud chose the kendhang ketipung as the instrument to begin his work as Street musician. He felt that he had never come across anyone performing with a kendhang in his day. The concepts of dangdut and humour were his next choice, as Sujud felt that both of these factors coul relate closely to the community, and were also practical media for entertaining the community, which was Sujudc main goal in his profession.Keyword:Â  the concepts of Sujudâ€™s creativity